Morphological Processes in Online Game Terminology: A Study of IESF 2022 Casters - Mudhoffar, Ahmad (Journal of Literature, Linguistics, & Cultural Studies, 2024)
In the dynamic realm of the digital landscape, the internet has significantly shaped the lexicon of online gaming, giving rise to distinctive linguistic expressions within the gaming community. This study explores the morphological processes behind the online game terminology employed by casters during the IESF 2022 Mobile Legends: Bang-Bang tournament. Employing a qualitative descriptive approach, the research centers on the vocabulary used in the tournament's final match between the Philippines and Indonesia, as showcased on the Garudaku ESI YouTube channel. Analyzing 39 game terms through Yule's (2010) word formation theory, the study unveils various morphological processes, encompassing 7 instances of compounding, 1 of clipping, 7 of acronyms, and 24 of derivation. These findings underscore the dynamic and innovative facets of language evolution in the digital era, emphasizing the ongoing transformation within the E-sports domain. This research underscores the significance of continual linguistic exploration in the realm of online gaming, advocating for diverse theoretical approaches to better understand the fluid and ever-changing nature of language in digital contexts. The insights garnered in this study lay a foundation for future linguistic analyses in Mobile Legends tournaments and analogous online environments, contributing to the broader understanding of the linguistic intricacies that characterize these digital spaces.